Pelatihan Pemberdayaan Media Sosial untuk Meningkatkan Brand Awareness pada UMKM Alami Telur Asin (ATA) - Halimah, Siti Nur; Husna, Siti Nuril Septaniatul; Zunaidi, Arif; Siti Roudhoh; Khoiriyati, Soibathul; Putri, Tia Rizka; Latifah, Yunisa Shindi; Janah, Sidanatul (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service aims to provide support to Natural Salted Egg MSMEs (ATA) in optimizing the potential of electronic commerce (e-commerce) and strengthening their presence through social media. The ABCD (asset-based community development) approach is applied in the service methodology, involving preparation stages, discussions, product creation assistance, creating e-commerce and social media accounts, product photo training, e-commerce and social media management, as well as assistance on the marketplace platform and social media such as Grab and Shopee. The results of the activities include increasing partners' knowledge regarding online marketing strategies, expanding target markets, and increasing sales turnover of Natural Salted Egg (ATA) MSME products. E-commerce and social media have proven to be effective tools for increasing brand awareness, expanding marketing reach, and increasing online marketing efficiency. Thus, this service has a significant positive impact on the progress of Natural Salted Egg (ATA) MSMEs in facing the challenges of the digital trade era.